Effect of Rubber Seed Meal (Hevea brasiliensis) on Blood Biochemical Parameters and Enzyme Profiles of Broiler Birds - Debbarma, Gourab; Samanta, A. K.; Buragohain, Rajat; Das, Biren Kumar; Behera, Parthasarathi; Debbarma, Merion; Paul, Akash (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted at Department of Animal Nutrition in C.V.Sc. & A.H., C.A.U., Aizawl, Mizoram, in the month of September to November, 2022 to assess the effect of feeding rubber seed meal (Hevea brasiliensis) on biochemical parameters and enzyme profiles of broiler birds. 200 one-day old broiler chicks were purchased from commercial broiler chick distributor of Aizawl city, Mizoram. The chicks were distributed randomly into four experimental groups in a Completely Randomized Block Design. 50 birds of each group were further divided into five replicate with ten chicks in each replicate. The Group-1, Group-2, Group-3 and Group-4 were fed with standard basal ration formulated as per BIS (2007), standard basal ration with 10%, 15% and 20% replacement of maize with rubber seed meal, respectively. Overnight water soaked rubber seed was dried and incorporated in the diet of broiler birds as replacement of maize. The rubber seed were collected from Tripura and were subjected to grinding followed by water soaking for overnight, sun drying for 5–7 days and incorporated in the diet of the broiler birds. Feeding trial was conducted for 42 days. Blood biochemical parameters did not show any significant difference (p>0.05) between different treatment groups. ALT and AST values were not found significantly different (p>0.05) among different treatment groups. It can be concluded that rubber seed meal can be incorporated in the diet as a replacement of maize up to 20% without adversely affecting blood biochemical and enzyme profiles of broiler chickens